Sustainable strategies for hospital wastewater treatment: bioremediation, phytoremediation, and hybrid approaches for emerging pollutants - Sharma, Shubhra; Prakash, Divya; Agnihotri, Swarnima (Frontiers in Microbiology, 2026)
Hospital wastewater (HWW) is a complex matrix of pharmaceutical residues, antibiotic resistance genes (ARGs), pathogens, and emerging contaminants that threaten public health and ecosystems. Conventional wastewater treatment plants (WWTPs) often fail to eliminate persistent compounds like carbamazepine and sulfamethoxazole, contributing to antimicrobial resistance and environmental toxicity. This review explores advanced treatment strategies with a focus on bioremediation and phytoremediation. Microbial approaches using bacteria, fungi, algae such as Labrys portucalensis, Trametes versicolor, and Chlorella vulgaris demonstrate degradation of pharmaceuticals and ARGs. Similarly, phytoremediation with species like Typha angustifolia and Vetiveria zizanioides supports on-site through rhizospheric uptake. Integrated systems combining membrane bioreactors (MBRs), advanced oxidation processes (AOPs), constructed wetlands (CWs), and microbial consortia offer enhanced removal efficiency and ARG reduction. While hybrid systems show strong potential, they face challenges such as high costs, difficulties in large-scale application, and limited regulation. Overall, this review highlights how integrating biological and technological methods provides a practical and sustainable path forward for treating hospital wastewater (HWW) and reducing its environmental and health impacts. A multidisciplinary, globally coordinated approach is essential for sustainable HWW management.